Endocannabinoids Mediate Muscarinic Acetylcholine Receptor-Dependent Long-Term Depression in the Adult Medial Prefrontal Cortex - Martin, Henry G. S.; Bernabeu, Axel; Lassalle, Olivier; Bouille, Clément; Beurrier, Corinne; Pelissier-Alicot, Anne-Laure; Manzoni, Olivier J. (Frontiers in Cellular Neuroscience, 2015)
Cholinergic inputs into the prefrontal cortex (PFC) are associated with attention and cognition; however there is evidence that acetylcholine also has a role in PFC dependent learning and memory. Muscarinic acetylcholine receptors (mAChR) in the PFC can induce synaptic plasticity, but the underlying mechanisms remain either opaque or unresolved. We have characterized a form of mAChR mediated long-term depression (LTD) at glutamatergic synapses of layer 5 principal neurons in the adult medial PFC. This mAChR LTD is induced with the mAChR agonist carbachol and inhibited by selective M1 mAChR antagonists. In contrast to other cortical regions, we find that this M1 mAChR mediated LTD is coupled to endogenous cannabinoid (eCB) signaling. Inhibition of the principal eCB CB1 receptor blocked carbachol induced LTD in both rats and mice. Furthermore, when challenged with a sub-threshold carbachol application, LTD was induced in slices pretreated with the monoacylglycerol lipase inhibitor JZL184, suggesting that the eCB 2-arachidonylglyerol (2-AG) mediates M1 mAChR LTD. Yet, when endogenous acetylcholine was released from local cholinergic afferents in the PFC using optogenetics, it failed to trigger eCB-LTD. However coupling patterned optical and electrical stimulation to generate local synaptic signaling allowed the reliable induction of LTD. The light – electrical pairing induced LTD was M1 mAChR and CB1 receptor mediated. This shows for the first time that connecting excitatory synaptic activity with coincident endogenously released acetylcholine controls synaptic gain via eCB signaling. Together these results shed new light on the mechanisms of synaptic plasticity in the adult PFC and expand on the actions of endogenous cholinergic signaling.